1999
DOI: 10.3354/meps185181
|View full text |Cite
|
Sign up to set email alerts
|

Possessing a poor anaerobic capacity does not prevent the diel vertical migration of Nordic krill Meganyctiphanes norvegica into hypoxic waters

Abstract: During their diel vertical migration in the Gullmarsfjord (Swedish west coast) Nordic krill Meganyctiphanes norvegica made excursions into regions of severe hypoxia, >7O m depth, dunng the day. Consequently, we investigated the capacity for anaerobic metabolism by M. norvegica and the extent to which they utilize this capacity in the field. L-lactate was the main end-product of anaerobic metabolism. The concentration of L-lactate in the haemolymph ([la~tate],,~) under conditions of acutely declining p 0 2 only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 27 publications
2
32
1
Order By: Relevance
“…Despite an earlier report which seemed to suggest that M. norvegica would not traverse a pycnocline into an area of low O 2 (Bergström and Strömberg, 1997), excursions into severely hypoxic bottom water (PO 2 ¼ 3-10 kPa at a depth of 65-85 m, roughly 15-50% O 2 saturation; the waters are hypoxic because of a delay, or sometimes cessation, in annual water renewal as a result of altered currents) in the Gullmarsfjord meant that krill during the day resided at such depths (Spicer et al, 1999). van den Thillart found that M. norvegica was able to regulate its O 2 uptake down to approx.…”
Section: Effects Of Hypoxia On O 2 Uptake and Anaerobic Metabolismmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite an earlier report which seemed to suggest that M. norvegica would not traverse a pycnocline into an area of low O 2 (Bergström and Strömberg, 1997), excursions into severely hypoxic bottom water (PO 2 ¼ 3-10 kPa at a depth of 65-85 m, roughly 15-50% O 2 saturation; the waters are hypoxic because of a delay, or sometimes cessation, in annual water renewal as a result of altered currents) in the Gullmarsfjord meant that krill during the day resided at such depths (Spicer et al, 1999). van den Thillart found that M. norvegica was able to regulate its O 2 uptake down to approx.…”
Section: Effects Of Hypoxia On O 2 Uptake and Anaerobic Metabolismmentioning
confidence: 99%
“…So in common with a number of other krill species M. norvegica displays some ability to maintain O 2 uptake in the face of declining O 2 tensions but the ability does not seem to be any more developed than that found in krill species which do not encounter hypoxia on a regular basis, if at all. Furthermore, M. norvegica is characterised by one of the poorest anaerobic capacities of any crustacean, surviving not more than 1 h in anoxia, and accumulating large concentrations of L-lactic acid quickly (Spicer et al, 1999). So reliance on a shift from aerobic Physiology and Metabolism of Northern Krill to anaerobic metabolism when exposed to low O 2 can barely be seen as an adaptation to migrating into hypoxic layers during DVM; indeed if krill are caged in deep hypoxic water for a greater period than they would normally reside there, they have extremely high levels of L-lactate if they survive, but survival itself is poor (Spicer et al, 1999).…”
Section: Effects Of Hypoxia On O 2 Uptake and Anaerobic Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have, in addition, revealed significant changes within the day. The Nordic krill Meganyctiphanes norvegica, like other Euphausiacea, adopts diel vertical migration moving from 100 m depth during the day to the surface layers during the night (Spicer et al, 1999). This organism, therefore, is cyclically exposed to environments that are characterized by different temperature, salinity, dissolved oxygen and food availability (Strömberg and Spicer, 2001).…”
Section: Absolute Variations: Changes Of Concentrationmentioning
confidence: 99%